Morphological and genetic relationships of the crocidura monticola species complex (soricidae: crocidurinae) in Sundaland - Hashim, Rosli; Ruedi, M.; Omar, H.; Bhassu, S. (2013)
Small Crocidurinae shrews (weight <8 g) from Southeast Asia have been poorly studied to date, mainly because of the difficulty to catch them and the concomitant paucity of reference specimens available in museums. Hence their systematics is still debated, and most small Crocidura shrews from Sundaland are assigned to the monticola species complex. Here, we report a study based on a survey of shrews caught with large pitfalls set on forest floors in Peninsular Malaysia. Morphometric analyses based on 14 skull measurements showed that these shrews tend to be larger with increasing altitude, but showed otherwise no consistent variation. When compared to museum specimens of the monticola species complex sampled in the Sundaland (total: 77 specimens), the Malay shrews tend also to be larger than those living on Kalimantan (Borneo) and Sumatra. All are, however, morphologically distinct from the other species, C. maxi, found in eastern Java and on the Lesser Sundas. Molecular analyses of a subset of these small shrews and based on a mitochondrial (cytochrome b) and a nuclear gene (Apolipoprotein B) suggest that samples from the central region of Peninsular Malaysia (Bukit Rengit and Ulu Gombak) genetically differ from other Malaysian populations (by about 7% K2P distance at the cyt b gene) and are more closely related to some samples from Sumatra and Borneo. These differences did not correlate with the altitudinal variation evidenced from the morphological analysis. Reference sequences from the terra typica of monticola and maxi (both species were originally described from Java) are however needed to determine if these unexpected genetic differences warrant additional taxonomic subdivision within the Sundaland. © 2013 Deutsche Gesellschaft für Säugetierkunde.